Analisis Aktor Politik Pembangunan Dalam Organisasi Al Washliyah Sumatera Utara - M. Fathin Arditri; Humaizi Humaizi; Heri Kusmanto (Universitas Medan Area, 2022)
The purpose of this study was to identify and understand the study, thoughts, roles and strategies of developmental political actors in the Al Washliyah organization conducted by DR.H. Dedi Iskandar Batubara, S.Sos, S.H, M.SP. The type of research used in this research is descriptive with a qualitative approach. Qualitative research methods are used to measure carefully certain social phenomena that occur. Specifically, this research method also uses the life history method. The results showed that as a political actor of development in the Al Washliyah organization in North Sumatra, where he played a role in the formation and optimization of acceleration in three Al Washliyah ittifaq charities, namely: Education; Da'wah; and Social Charity. The function of Dedi Iskandar Batubara as a development political actor in the Al Washliyah organization in North Sumatra is to improve organizational management which aims to synergize the programs formulated in the acceleration vision. The supporting factors for development political actors in the Al Washliyah organization in North Sumatra are the people (cadres) factor from strengthening human resources, where behind the implementation of a program will greatly determine the success or failure of a program and by utilizing digitalization (social media) which is a concept of information media in carrying out various activities, such as in the field of da'wah and meetings that can minimize the costs incurred and the efficiency of the time used. The inhibiting factor can be seen that there are not too big obstacles in translating various programs and work plans that have been mandated by the Al Wasliyah deliberations (Muktamar XIII).